2015
DOI: 10.3390/biom5020848
|View full text |Cite
|
Sign up to set email alerts
|

Structural Biology of Bacterial RNA Polymerase

Abstract: Abstract:Since its discovery and characterization in the early 1960s (Hurwitz, J. The discovery of RNA polymerase. J. Biol. Chem. 2005, 280, 42477-42485), an enormous amount of biochemical, biophysical and genetic data has been collected on bacterial RNA polymerase (RNAP). In the late 1990s, structural information pertaining to bacterial RNAP has emerged that provided unprecedented insights into the function and mechanism of RNA transcription. In this review, I list all structures related to bacterial RNAP (as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 88 publications
4
117
0
1
Order By: Relevance
“…High-resolution X-ray crystal structures are available for the T. aquaticus and E. coli RNA polymerases (12,14,16,18,20), and this proline occurs in the highly conserved D region that forms the RNA exit channel and in close proximity to amino acids found to complex with rifampin (16). The equivalent mutations of P564 in E. coli and P519 in S. aureus strain 8325-4 have been shown to confer high-level resistance to rifampin (16,24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution X-ray crystal structures are available for the T. aquaticus and E. coli RNA polymerases (12,14,16,18,20), and this proline occurs in the highly conserved D region that forms the RNA exit channel and in close proximity to amino acids found to complex with rifampin (16). The equivalent mutations of P564 in E. coli and P519 in S. aureus strain 8325-4 have been shown to confer high-level resistance to rifampin (16,24).…”
Section: Resultsmentioning
confidence: 99%
“…Structural studies of transcription initiation have revealed new insights into promoter recognition and the steps leading to open promoter formation (18,23,87,89). Promoter recognition is thought to be mediated by sigma factor-DNA interaction and core promoter elements comprising Ϫ35, Ϫ10, and extended Ϫ10 regions (12,23); however, a high-resolution study of an open promoter complex with Thermus thermophilus holoenzyme recently revealed the presence of a new determinant called the core recognition element (CRE) that is thought to provide sequence-specific promoter recognition of the Ϫ4 to ϩ2 region of the nontemplate DNA strand (89).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial RNAP holoenzyme nominally consists of 6 subunits: the ␤ and ␤= subunits that form the active site, an ␣ subunit dimer, an subunit, and a reversibly-binding subunit called (Fig. 1a) (Feklístov et al 2014;Murakami 2015;Ruff et al 2015). In most bacterial species, several different factors recognize cognate promoter sequences and ensure that all functional genes in the genome are expressed when required for cellular viability.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 18 years, and ongoing, impressive efforts in X-ray crystallography, transitioning to cryo-electron microscopy (cryo-EM), have provided deep insights into the structural biology of the cellular MSDDRPs, including their architecture, evolution, structure-function relationships, and dynamics. Growing numbers of such studies have covered the enzymes from bacteria (1,2), archaeal species (3)(4)(5), and eukaryotes , in various interaction states.…”
Section: Cellular Msddrpsmentioning
confidence: 99%